Factores Asociados al Desarrollo de Defectos Refractivos en la Etnia Hispana (2022)
En general, refractive errors occur first, myopia, followed by hyperopia and lastly astigmatism. Currently there are 21 countries where the Hispanic ethnic group settles, highlighting its geographical location not only in America, but also in part of Africa and Asia, becoming a population of economic and social relevance, of which the prevalence of states is not well defined. refractive disorders or the factors associated with their development.